Shattering Minds Experiences of Mental Illness in Modernist Finnish Literature - Ovaska, Anna (Studia Fennica Litteraria, 2023)
This study offers a new perspective on unusual and unsettling experiences that are often interpreted as "mental illnesses" and on the techniques through which literary representations invite readerly responses and engagement. The book examines how four Finnish modernist writers, Helvi Hämäläinen, Jorma Korpela, Timo K. Mukka, and Maria Vaara, construct experiences of shattering and distress as bodily experiences that are embedded in the social and material world and entangled with social and cultural norms that govern subjectivity, gender, and sexuality. Drawing on narrative theory, theories of embodied cognition, phenomenology of illness, and feminist theory, the analyses show how literary works can invite readers to respond emotionally and to reflect on our views of the human mind and its interaction with the world. The book sheds light on the fictional portrayals and techniques of representation and on the ethics of narrating and reading about painful experiences. It also illuminates the ways the mind, body, consciousness, and mental distress are discussed in Finnish modernist literature and situates the texts in the international modernist tradition.